PENGARUH PROPORSI BERAS DAN MAIZENA TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK PULI - Karjo, Stefani Karin; Suseno, Thomas Indarto Putut; Utomo, Adrianus Rulianto (Widya Mandala Surabaya Catholic University, 2015)
Starch is added in making kerupuk puli as puffable material which holds an important role in the expansive characteristic of the product. In this research, some proportion of rice will be substituted by corn starch as an attempt of diversifying kerupuk puli product in Indonesia. Randomized Block Design is used in this research in four replication, single factor (rice and maize proportion of 100:0, 95:5, 90:10, 85:15, 80:20, and 75:25). Parameters tested are physicochemical characteristics (water content, expansion volume, oil absorption, texture (Hardness and Fracturability)) and organoleptic characteristics (consumer preference test of crispness, taste, and color/visual appearance). Data will be analyzed using ANOVA (α=5%) and (DMRT) (α=5%) to determine the level of treatment which gives a significant difference. Maize has a different starch granule characteristics and amylose amylopectin proportion from rice, therefore it can be allegedly concluded that there will be differences in physicochemical and organoleptic characteristics of products. This research’s purpose is to determine a factor which gives the most preferred characteristic by the consumers. The obtained result shown that there were significant differences of water content of kerupuk before fried, expansion volume, oil absorption, Hardness, Fracturability, and consumer's preference of crispness between factors. The most favorable rice and maize proportion by objective test and consumer's preference test was 75:25, with water content of product before fried 11.48% (5.45% after fried), expansion volume 368.33%, oil absorption 43.32%, Hardness 5.633 N, Fracturability 0.498 N, and consumer's preferences score of color, taste, and crispness are 5.5854, 5.6439, and 5.9915.